Incentive effects of fiscal federalism: Evidence for France - Boriss Siliverstovs; Ulrich Thiessen (Cogent Economics & Finance, 2015)
This paper provides an empirical analysis on the question whether equalization payments across regions and transfers from the central government stimulate regional growth or impede it. Using a panel of 22 French regions from 2002 to 2008, we find that regional economic growth is positively affected by the fiscal equalization system. We employ two indicators of this system: the transfer volume measure (approximated by either tax revenues in other regions or transfers to regions) and the marginal retention rate. Our main finding is that the transfer volume effect is positive for growth in both donor and recipient regions. Hence, we do not find any evidence that regional governments in France allocate transfers inefficiently. This finding contradicts previous empirical studies for federal countries that tend to find adverse incentive effects of fiscal equalization on regional governments and growth. A major explanation behind this result could be that the volume of the transfers in France may appear to be relatively moderate, i.e. small enough to avoid adverse effects.
Keywords: E62; H70; R11; 330; fiscal equalization; intergovernmental transfers; French regions; decentralization